Development of Screening Parameter for the Design of Monolithic Alternative Landfill Covers in Arid and Semi-Arid Climates - Escobar, Francisco; Abichou, Tarek (Journal of Environmental Science and Engineering Technology, 2016)
After landfills reach their storage limit, they need to have a final cover to reduce the amount of water that percolates from rainfall to diminish leachate production and the risk of additional contamination. Many States require that final covers provide the hydraulic impedance that limits flow into underlying contaminated materials. Water balance covers that rely on the capacity of fine-textured soils to store infiltration during rainier periods have been accepted to be used in arid and semiarid climatic zones of the US. The objective of the study was to develop a screening parameter that will make alternative landfill cover design simpler. This study assessed how effective are previous design schemes and developed a new design index for water balance covers in Arid and Semi-Arid climates. Eighteen locations were selected across the Arid and Semi-Arid climate of the U.S. Ten typical soils were selected as representative of soils found in these regions. HYDRUS-1D was used as the model to simulate the water balance of several covers, each one for a different soil and thickness. The results of the simulation were compared to that expected using previous design schemes. Surprisingly, Ten out of eighteen modeled locations resulted in percolation, which contradicts existing design methodologies. A new design parameter, SrNEW, was developed by modifying the original SrACAP to be specific to alternative covers in Arid and Semi-Arid climates.